Method for improving lubricating property and wear resistance of base oil and method for improving dispersion stability of graphite in base oil
By using remote claw polymers in base oil to form supramolecular oil gels and performing π-π stacking interaction with graphite, graphite is peeled into graphene in situ, solving the toxicity and instability of existing lubricating oil additives and the poor stability of graphite dispersion, and achieving efficient lubricating and wear resistance.
Patent Information
- Application Number
- CN202311134300.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
AI Technical Summary
The existing lubricant additives have toxicity and instability problems, and the dispersion stability of graphite in the base lubricant is poor, which affects its tribological properties.
Remote claw polymer is used to form supramolecular oil gel in base oil, and the lubricating performance and wear resistance are improved through π-π stacking interaction. Through the π-π stacking interaction of remote claw polymer and graphite, graphite is peeled into graphene in situ to improve the dispersion stability of graphite.
It significantly improves the lubricating performance and wear resistance of base oil, reduces the aggregation and precipitation of graphite in base oil, improves the dispersion stability of graphite, and is low in cost and easy to use.
Smart Images

Figure CN119570544A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supramolecular chemistry, and specifically relates to a method for improving the lubrication performance and anti-wear performance of base oil and a method for improving the dispersion stability of graphite in base oil. Background Art
[0002] Friction and wear are ubiquitous in mechanical systems and can cause huge energy losses. The best way to reduce friction and wear is to lubricate the moving parts of a mechanical system. Lubricating oil is an effective medium for achieving lubrication, which can effectively reduce friction and wear, thereby significantly improving the energy efficiency and service life of the machine. Lubricating additives are the key to lubricating oils. Traditional additives include phosphorus and sulfur compounds and organic metal complexes, which can form a protective friction film on the friction surface to prevent direct contact between machine parts. However, the toxicity of these molecular additives themselves and their inherent instability under chemical, thermal and / or mechanical conditions have led to serious emissions of harmful substances, thus causing environmental problems. Therefore, exploring ways to improve lubrication and anti-wear properties has always been one of the research topics in mechanical systems.
[0003] In contrast, nanoparticles as lubricant additives not only have low toxicity and high stability, but also show excellent tribological properties in terms of friction reduction and anti-wear. For example, graphite derivatives such as graphene, graphene oxide, and reduced graphene oxide have two-dimensional (2D) nanostructures, weak van der Waals or π-π interactions between layers, and high mechanical strength within the same layer. These features make it easy for adjacent layers to slip against each other under shear stress without destroying the intralayer structure. Therefore, they have been recognized as nanoadditives in base oils that can effectively reduce friction and wear. However, the application of these derivatives requires a series of complex pretreatment processes starting from the original graphite, which makes it more expensive as a lubricant additive. Therefore, in actual tribological applications, the original graphite is directly used as a lubricant additive. However, the dispersion stability of graphite in the base lubricant is poor, which will reduce its tribological properties. Summary of the invention
[0004] In view of the above technical status, a technical objective of the present invention is to improve the lubrication performance and anti-wear performance of base oil.
[0005] In order to achieve the above technical objectives, the inventors have discovered a telechelic polymer after a long period of extensive research and exploration, which has good application prospects in the field of mechanical lubrication. The telechelic polymer is a polymethacrylate long-chain alkyl ester containing pyrene groups at both ends, denoted as P m S 2n P m, wherein the P block comprises 2-(1-pyrenebutanoyloxy)ethyl methacrylate monomer, the S block is an oil-soluble long-chain alkyl polymethacrylate, m is the degree of polymerization of the P block, and 2n is the degree of polymerization of the S block.
[0006] m is an integer, and its value is not limited. Preferably, m is an integer selected from 5 to 10, including 5 and 10.
[0007] 2n is an integer, and its value is not limited. Preferably, 2n is an integer selected from 10 to 500, including 10 and 500; more preferably, 2n is an integer selected from 10 to 100, including 10 and 100, such as 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc.
[0008] The long-chain alkyl polymethacrylate is not limited, and includes lauryl polymethacrylate and octadecyl polymethacrylate.
[0009] The preparation method of the telechelic polymer is not limited, including using a macromolecular initiator bifunctionalized with a long-chain alkyl polymethacrylate to obtain a telechelic polymer functionalized with hydroxyl groups at both ends by controlled ATRP polymerization, and then obtaining a telechelic polymer functionalized with pyrene groups at both ends by esterification reaction. The preparation method includes the following steps:
[0010] (1) Synthesis of long-chain alkyl polymethacrylate based on bifunctional initiators;
[0011] (2) Using long-chain alkyl polymethacrylate as a macromolecular ATRP initiator to synthesize dual-terminal hydroxyl-functionalized telechelic polymers;
[0012] The hydroxyl group is not limited, and includes hydroxyethyl methacrylate and 2-methyl-2-acrylate-2,3-dihydroxypropyl ester (3) through esterification reaction to obtain the pyrene functionalized telechelic polymer.
[0013] The inventors have found that when the telechelic polymer of the present invention is dispersed in a base oil, a supramolecular oil gel is formed through π-π stacking interaction. The supramolecular oil gel has good lubrication and anti-wear properties. Compared with the base oil, the lubrication and anti-wear properties can be improved, and therefore it can be used as a lubricating oil.
[0014] That is, the technical solution of the present invention is: a method for improving the lubricity and anti-wear properties of a base oil, characterized by: dispersing a telechelic polymer in a base oil to form a supramolecular oil gel through π-π stacking interaction;
[0015] The telechelic polymer is a polymethacrylate long-chain alkyl ester containing pyrene groups at both ends, denoted as P m S 2n Pm , wherein the P block comprises 2-(1-pyrenebutanoyloxy)ethyl methacrylate monomer, the S block is an oil-soluble long-chain alkyl polymethacrylate, m is the degree of polymerization of the P block, and 2n is the degree of polymerization of the S block.
[0016] The base oil is not limited, including mineral oil, synthetic oil and vegetable oil. Mineral oil is refined from crude oil. Synthetic oil is synthesized by chemical methods, such as poly-α-olefins. Vegetable oil is obtained from the fruits, seeds, germs, etc. of plants.
[0017] When the telechelic polymer is dispersed in the base oil, the mass percentage concentration of the telechelic polymer is not limited, and is preferably 2-20%, more preferably 5-10%, such as 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0018] Preferably, during the formation of the supramolecular oil gel, the base oil solution is heated at a temperature of 10-40°C, preferably 15-30°C, such as 15°C, 20°C, 25°C, 30°C, etc.
[0019] Preferably, during the formation of the supramolecular oil gel, the base oil solution is stirred, and more preferably, ultrasonic stirring is used.
[0020] The supramolecular oil gel has good lubrication and anti-wear properties. For example, when dispersed in the base oil PAO-10, the friction coefficient of the formed supramolecular oil gel under the friction conditions of a load of 200N and a frequency of 25Hz is less than 0.125.
[0021] Preferably, a lubricating oil additive is also dispersed in the base oil to further improve the lubrication performance and anti-wear performance.
[0022] The lubricating oil additive is not limited, and includes graphite and its derivatives, such as graphene, graphene oxide, reduced graphene oxide, etc.
[0023] Preferably, when dispersed in the base oil, the mass percentage concentration of the lubricating oil additive is 0.2-5%, more preferably 0.5-2.5%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, etc.
[0024] In addition, the inventors have found that when the lubricating oil additive is graphite, the graphite can be in-situ exfoliated into graphene under the assistance of ultrasound through the π-π stacking interaction between the telechelic polymer pyrene group and the graphite. This is not only low-cost and simple and easy to implement, but also improves the dispersion stability of graphite in the base oil, and solves the problem of poor dispersion stability of graphite in the base lubricating oil, aggregation and precipitation.
[0025] That is, another technical solution provided by the present invention is: a method for improving the dispersion stability of graphite in base oil, wherein telechelic polymer and graphite are dispersed in base oil, a supramolecular oil gel is formed through π-π stacking interaction, and under the assistance of ultrasound, π-π stacking interaction is formed between the pyrene group of the telechelic polymer and the graphite, and the graphite is in-situ exfoliated into graphene;
[0026] The telechelic polymer is a polymethacrylate long-chain alkyl ester containing pyrene groups at both ends, denoted as P m S 2n P m , wherein the P block comprises 2-(1-pyrenebutanoyloxy)ethyl methacrylate monomer, the S block is an oil-soluble long-chain alkyl polymethacrylate, m is the degree of polymerization of the P block, and 2n is the degree of polymerization of the S block.
[0027] Compared with the prior art, the telechelic polymer of the present invention is composed of an oil-soluble central chain and two pyrene functionalized end chains, such as Figure 1 As shown, they can self-assemble into a fully cross-linked, rod-shaped, stable micelle (gel) network through π-π stacking interactions, which has the following beneficial effects:
[0028] (1) The telechelic polymer is mixed with a base oil, and can self-assemble into a completely cross-linked, rod-shaped, stable oil gel network through π-π stacking interaction to form a stable oil gel, which can significantly alleviate the leakage and creeping of the base oil and improve the stability of the base oil. On the other hand, it can improve the lubrication and anti-wear properties of the base oil, so it can be used as a friction-reducing and anti-wear lubricant in mechanical systems. For example, when dispersed in the base oil PAO-10, the friction coefficient of the formed supramolecular oil gel under the friction conditions of a load of 200N and a frequency of 25Hz is less than 0.125.
[0029] (2) When the telechelic polymer of the present invention is added to the base oil and a lubricant additive is added, the lubrication performance and anti-wear performance of the resulting lubricant can be further improved. The lubricant additive includes but is not limited to graphite or its derivatives, such as graphene, graphene oxide, etc. For example, when dispersed in the base oil PAO-10, the friction coefficient of the oil gel under the friction conditions of a load of 200N and a frequency of 25Hz is less than 0.12.
[0030] (3) When the lubricating oil additive is graphite, the π-π stacking interaction between the pyrene-containing groups in the telechelic polymer and the graphite can exfoliate the graphite into graphene in situ under the assistance of ultrasound. This is not only low-cost and simple, but also improves the dispersion stability of graphite in the base oil, solving the problem of poor dispersion stability of graphite in the base lubricating oil, aggregation and precipitation. Experiments have confirmed that the supramolecular oil gel formed by dispersing the telechelic polymer and graphite in the base oil has good long-term stability. At 20°C, the oil gel does not show any visible fluidity after being stored for one year; and the lubrication and anti-wear properties of the supramolecular oil gel are comparable to those of the supramolecular oil gel formed by dispersing the telechelic polymer and graphene in the base oil. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is the synthesis route of the telechelic polymer in Examples 1-3 of the present invention.
[0032] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the telechelic polymer in Example 1 of the present invention.
[0033] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of the telechelic polymer in Example 2 of the present invention.
[0034] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the telechelic polymer in Example 3 of the present invention.
[0035] Figure 5 is the gel permeation chromatogram of the telechelic polymer in Examples 1-3 of the present invention.
[0036] Figure 6 It is a molecular dynamic diagram of the oil gel in Examples 4-6 of the present invention.
[0037] Figure 7 It is an inverted appearance diagram of the oil gel in Examples 5 and 8 of the present invention.
[0038] Figure 8 It is the morphology of the original graphite in Comparative Example 1 of the present invention and the graphite in Examples 7-9 after being exfoliated into graphene.
[0039] Fig. 9 It is a graph showing the test results of the friction coefficient of the oil gel samples in Examples 4-9 of the present invention and the PAO-10 base oil sample.
[0040] Fig.10 It is a wear scar volume test diagram of the oil gel samples of Examples 4-9 of the present invention and the PAO-10 base oil sample under the same friction conditions.
[0041] Fig.11 It is a graph showing the test results of the friction coefficient of the oil gel samples in Examples 10-12 of the present invention and the PAO-10 base oil sample.
[0042] Fig.12 It is a wear scar volume test diagram of the oil gel samples in Examples 10-12 of the present invention and the PAO-10 base oil sample under the same friction conditions.
[0043] Fig.13 It is a graph showing the test results of the friction coefficient of the oil gel samples and the PAO-10 base oil sample in Examples 13-15 of the present invention.
[0044] Fig.14 It is a wear scar volume test diagram of the oil gel samples in Examples 13-15 of the present invention and the PAO-10 base oil sample under the same friction conditions. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with the embodiments and drawings. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.
[0046] Embodiment 1:
[0047] In this embodiment, the telechelic polymer structure is as follows:
[0048]
[0049] Wherein, m=6, n=15, is a telechelic polymer P6S formed by functionalizing 2-(1-pyrenebutyryloxy)ethyl methacrylate at both ends of poly(octadecyl methacrylate) 30 P6.
[0050] The preparation method of the polymer is as follows Figure 1 As shown, the double-headed poly(octadecyl methacrylate) S was synthesized by using hydroquinone as a bifunctional initiator. 30 , and then through the macroinitiator S 30 Synthesis of Telechelic Polymer H6S Functionalized with Hydroxyl Groups at Both Ends 30 H6, and finally synthesize the target product P6S through esterification reaction 30 P6. Specifically includes the following steps:
[0051] (1) Macroinitiator S 30 Synthesis of:
[0052] First, the Schlenk flask was evacuated to vacuum with a vacuum pump, and argon was passed through for three cycles. Then, di(2-bromoisobutyric acid)-1,4-phenyl diester (160 mg, 1.23 mmol) and octadecyl methacrylate (4 g, 11.8 mmol) were dissolved in a mixture of 6 g toluene and N,N,N',N',N"-pentamethyldiethylenetriamine (330 μL, 0.79 mmol), and the mixed solution was added to the bottle. Next, cuprous bromide (68 mg, 0.47 mmol) was quickly added under an argon atmosphere. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. . The reaction mixture was then stirred in an oil bath preheated to 70°C for 2 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected and the solution was concentrated to about 5 mL by rotary evaporation. It was added dropwise to 200 mL of cold acetone for precipitation. This precipitation process was repeated three times to completely remove the methacrylate octadecyl monomer, thereby purifying the polymer. The resulting solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 3.0 g, 75%.
[0053] (2)H6S 30 Synthesis of H6:
[0054] The Schlenk flask was evacuated with a vacuum pump, and then argon was introduced for 3 cycles. 30 (500 mg) was dissolved in 10 mL THF, and then hydroxyethyl methacrylate (0.192 g, 1.47 mmol) N,N,N',N',N"-pentamethyldiethylenetriamine (40.0 μL, 0.20 mmol) was added, and the mixed solution was quickly added to the reaction flask. Under an argon atmosphere, cuprous bromide (20 mg, 0.14 mmol) was further added. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. The reaction mixture was then reacted at 65°C for 10 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected, the solution was concentrated to about 5 mL by rotary evaporation, and dropped into 200 mL of cold acetone for precipitation to purify the polymer. The obtained solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 513 mg, 74%.
[0055] (3)P6S 30 Synthesis of P6:
[0056] H6S 30H6 (500 mg), 1-pyrenebutyric acid (612 mg) and DMAP (52 mg) were dissolved in 20 mL CH2Cl2, and the mixed solution was placed in an ice bath. EDC (412 mg) was then dissolved in 10 mL CH2Cl2 and added dropwise to the mixed solution and stirred for 2 hours. The reaction was then stirred at room temperature for 24 hours and precipitated in acetone to obtain the final product P6S. 30 P6. The obtained solid was dried under reduced pressure at room temperature for 12 hours. Yield: 410 mg, 81%.
[0057] The H NMR spectrum of the sample is Figure 2 As shown, it is confirmed that P6S 30 The successful synthesis of P6 solid sample and the calculation of P6S 30 Molecular weight of P6 solid sample M n,NMR It is 15400g / mol.
[0058] The gel permeation chromatography of the sample was Figure 5 As shown in a, it is confirmed that the molecular weight of the sample is M n,SEC is 16400 g / mol, and P6S is calculated 30 The molecular weight distribution of the P6 solid sample was 1.18.
[0059] Embodiment 2:
[0060] In this embodiment, the polymer structure is substantially the same as that in Example 1, wherein m=6, n=25, and is a telechelic polymer P6S formed by functionalizing 2-(1-pyrenebutyryloxy)ethyl methacrylate at both ends of poly(octadecyl methacrylate). 50 P6.
[0061] The preparation method of the polymer is as follows Figure 1 As shown, the double-headed poly(octadecyl methacrylate) S was synthesized by using hydroquinone as a bifunctional initiator. 50 , and then through the macroinitiator S 50 Synthesis of Telechelic Polymer H6S Functionalized with Hydroxyl Groups at Both Ends 50 H6, and finally synthesize the target product P6S through esterification reaction 50 P6. Specifically includes the following steps:
[0062] (1) Macroinitiator S 50 Synthesis of:
[0063] First, the Schlenk flask was evacuated to vacuum with a vacuum pump, and then argon was passed through for three cycles. Then, di(2-bromoisobutyric acid)-1,4-phenyl diester (95 mg, 0.236 mmol) and octadecyl methacrylate (4 g, 11.8 mmol) were dissolved in a mixture of 6 g toluene and N,N,N',N',N"-pentamethyldiethylenetriamine (100 μL, 0.47 mmol), and the mixed solution was added to the bottle. Next, cuprous bromide (41 mg, 0.28 mmol) was quickly added under an argon atmosphere. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. . The reaction mixture was then stirred in an oil bath preheated to 70°C for 2 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected and the solution was concentrated to about 5 mL by rotary evaporation. It was added dropwise to 200 mL of cold acetone for precipitation. This precipitation process was repeated three times to completely remove the methacrylate octadecyl monomer, thereby purifying the polymer. The resulting solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 3.2 g, 81%.
[0064] (2)H6S 50 Synthesis of H6:
[0065] The Schlenk flask was evacuated with a vacuum pump, and then argon was introduced for 3 cycles. 50 (500 mg) was dissolved in 10 mL THF, and then hydroxyethyl methacrylate (0.115 g, 0.886 mmol) N,N,N',N',N"-pentamethyldiethylenetriamine (40.0 μL, 0.20 mmol) was added, and the mixed solution was quickly added to the reaction flask. Under an argon atmosphere, cuprous bromide (20 mg, 0.14 mmol) was further added. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. The reaction mixture was then reacted at 65°C for 10 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected, the solution was concentrated to about 5 mL by rotary evaporation, and dropped into 200 mL of cold acetone for precipitation to purify the polymer. The resulting solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 504 mg, 82%.
[0066] (3)P6S 50 Synthesis of P6:
[0067] H6S 50H6 (500 mg), 1-pyrenebutyric acid (468 mg) and DMAP (40 mg) were dissolved in 20 mL CH2Cl2, and the mixed solution was placed in an ice bath. EDC (311 mg) was then dissolved in 10 mL CH2Cl2 and added dropwise to the mixed solution and stirred for 2 hours. The reaction was then stirred at room temperature for 24 hours and precipitated in acetone to obtain the final product P6S. 50 P6. The obtained solid was dried under reduced pressure at room temperature for 12 hours. Yield: 420 mg, 84%.
[0068] The H NMR spectrum of the sample is shown in Figure 3 As shown, it is confirmed that P6S 50 The successful synthesis of P6 solid sample and the calculation of P6S 50 Molecular weight of P6 solid sample M n,NMR It is 22200g / mol.
[0069] The gel permeation chromatography of the sample was Figure 5 As shown in b, it is confirmed that the molecular weight of the sample is M n,SEC is 21600 g / mol, and P6S is calculated 50 The molecular weight distribution of the P6 solid sample was 1.11.
[0070] Embodiment 3:
[0071] In this embodiment, the polymer structure is substantially the same as that in Example 1, wherein m=6, n=35, and is a telechelic polymer P6S formed by functionalizing 2-(1-pyrenebutyryloxy)ethyl methacrylate at both ends of poly(octadecyl methacrylate). 70 P6.
[0072] The preparation method of the polymer is as follows Figure 1 As shown, the double-headed poly(octadecyl methacrylate) S was synthesized by using hydroquinone as a bifunctional initiator. 70 , and then through the macroinitiator S 70 Synthesis of Telechelic Polymer H6S Functionalized with Hydroxyl Groups at Both Ends 70 H6, and finally synthesize the target product P6S through esterification reaction 70 P6. Specifically includes the following steps:
[0073] (1) Macroinitiator S 70 Synthesis of:
[0074] First, the Schlenk flask was evacuated to vacuum with a vacuum pump, and then argon was passed through for three cycles. Then, di(2-bromoisobutyric acid)-1,4-phenyl diester (68 mg, 0.168 mmol) and octadecyl methacrylate (4 g, 11.8 mmol) were dissolved in a mixture of 6 g toluene and N,N,N',N',N"-pentamethyldiethylenetriamine (70 μL, 0.34 mmol), and the mixed solution was added to the bottle. Next, cuprous bromide (28 mg, 0.20 mmol) was quickly added under an argon atmosphere. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. The reaction mixture was then stirred in an oil bath preheated to 70°C for 2 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected and the solution was concentrated to about 5 mL by rotary evaporation. It was added dropwise to 200 mL of cold acetone for precipitation. This precipitation process was repeated three times to completely remove the methacrylate octadecyl monomer, thereby purifying the polymer. The resulting solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 3.1 g, 78%.
[0075] (2)H6S 70 Synthesis of H6:
[0076] The Schlenk flask was evacuated with a vacuum pump, and then argon was introduced for 3 cycles. 50 (500 mg) was dissolved in 10 mL THF, and then hydroxyethyl methacrylate (0.0823 g, 0.633 mmol) N,N,N',N',N"-pentamethyldiethylenetriamine (40.0 μL, 0.20 mmol) was added, and the mixed solution was quickly added to the reaction flask. Under an argon atmosphere, cuprous bromide (20 mg, 0.14 mmol) was further added. The oxygen in the reaction system was removed by three freeze-vacuum-thaw cycles. The reaction mixture was then reacted at 65°C for 10 hours. After the reaction was completed, the round-bottom flask was placed in ice water and the reaction was opened to the air to terminate the reaction. After passing through a neutral alumina column to remove cuprous bromide, the eluent was collected, the solution was concentrated to about 5 mL by rotary evaporation, and dropped into 200 mL of cold acetone for precipitation to purify the polymer. The resulting solid was dried under reduced pressure at room temperature for 12 hours, with a yield of 436 mg, 75%.
[0077] (3)P6S 70 Synthesis of P6:
[0078] H6S 70H6 (500 mg), 1-pyrenebutyric acid (392 mg) and DMAP (33 mg) were dissolved in 20 mL CH2Cl2, and the mixed solution was placed in an ice bath. EDC (261 mg) was then dissolved in 10 mL CH2Cl2 and added dropwise to the mixed solution and stirred for 2 hours. The reaction was then stirred at room temperature for 24 hours and precipitated in acetone to obtain the final product P6S. 70 P6. The obtained solid was dried under reduced pressure at room temperature for 12 hours, yield: 425 mg, 85%.
[0079] The H NMR spectrum of the sample is shown in Figure 4 As shown, it is confirmed that P6S 70 The successful synthesis of P6 solid sample and the calculation of P6S 70 Molecular weight of P6 solid sample M n,NMR It is 28900g / mol.
[0080] The gel permeation chromatography of the sample was Figure 5 As shown in c, it is confirmed that the molecular weight of the sample is M n,SEC is 27800 g / mol, and H6S is calculated 70 The molecular weight distribution of the H6 solid sample was 1.13.
[0081] Embodiment 4-6:
[0082] In this example, the telechelic polymer P6S in Example 1-3 30 P6, P6S 50 P6 and P6S 70 P6 solid samples were dispersed in poly-α-olefin-10 (PAO-10) base oil, and the concentration of telechelic polymer was 6.0wt%. The base oil solution was heated and ultrasonically treated. At 20°C, π-π stacking interactions occurred between the pyrene groups to form oil gel P6S 30 P6, P6S 50 P6, P6S 70 P6, dynamic oil gel structure such as Figure 6 shown.
[0083] These oil gels are gel-like in appearance and have no fluidity. Inversion experiments show that they do not show any visible fluidity after being stored at 20°C for one year. They have good stability and can significantly alleviate the leakage and creeping that are common in base oils. As an example, Figure 7 The left figure shows the oil gel P6S in Example 5 50 The inversion test results of P6 are similar to those of the oil gels in Examples 4 and 6.
[0084] Comparative Example 1:
[0085] This example is a comparative example to the following examples 7-9.
[0086] In this embodiment, graphite is uniformly dispersed in poly alpha-olefin-10 (PAO-10) base oil, the concentration of graphite is 1.2wt%, and when it is left to stand for a certain period of time at 20°C, the graphite nanoparticles will obviously aggregate and settle at the bottom of the bottle. As an example, Figure 7 The right figure in FIG. 1 is a still picture of graphite in base oil in Comparative Example 1, showing that graphite aggregation and sedimentation occurred in the base oil.
[0087] Embodiment 7-9:
[0088] This example is basically the same as Comparative Example 1, except that the telechelic polymer solid sample in Examples 1-3 is also dispersed in poly-α-olefin-10 (PAO-10) base oil, and the telechelic polymer and graphite undergo π-π stacking to obtain supramolecular oil gel. The specific method is as follows:
[0089] Graphite was dispersed in poly alpha olefin-10 (PAO-10) base oil, and the telechelic polymer P6S 30 P6, P6S 50 P6 or P6S 70 The P6 solid sample was also dispersed in a poly-α-olefin-10 (PAO-10) base oil. The concentration of the telechelic polymer in the base oil solution was 6.0 wt % and the concentration of graphite was 1.2 wt %. The base oil solution was heated and ultrasonically treated to form an oil gel Graphite@P6S at 20 ° C. 30 P6, Graphite@P6S 50 P6 and Graphite@P6S 70 P6.
[0090] These oil gels are gel-like in appearance and have no fluidity. Inversion experiments show that they do not show any visible fluidity when stored at 20°C for one year, indicating good stability. Figure 7 The middle picture is the oil gel Graphite@P6S in Example 8 50 The inversion test results of P6 show that the addition of telechelic polymer improves the dispersion stability of graphite in the base oil and solves the problem of its agglomeration and precipitation. The inversion test results of the oil gels in Examples 8 and 9 are similar.
[0091] The morphology of the original graphite is shown in Figure 8 As shown in the left figure, the graphite morphology in Examples 7-9 is as follows Figure 8 As shown in the middle right figure, it is shown that after adding the telechelic polymer in Examples 7-9, the graphite is exfoliated into graphene.
[0092] The oil gel and PAO-10 base oil samples in Examples 4-9 were subjected to SRV-IV vibration reciprocating friction test under the following test conditions: load 200N, frequency 25Hz, amplitude 1000μm, cycle 30min, temperature 20°C. The test results are shown in Fig. 9 As shown, the details are as follows:
[0093] (1) Compared with the PAO-10 base oil, the friction coefficients of the oil gels in Examples 4-9 are all reduced, indicating that the addition of the telechelic polymer P6S to the PAO-10 base oil 30 P6, P6S 50 P6 and P6S 70 P6 can greatly improve its lubricating properties, that is, the oil gels in Examples 4-9 can be used as lubricating oils.
[0094] (2) Compared with adding telechelic polymer to base oil, adding not only telechelic polymer but also graphite to base oil can further improve lubrication performance. For example, in Example 4, P6S 30 The friction coefficient of P6 is 0.123. 30 The friction coefficient of P6 is 0.119. 50 The friction coefficient of P6 is 0.123. 50 The friction coefficient of P6 is 0.118. 70 The friction coefficient of P6 is 0.124. In Example 9, Graphite@P6S 70 The friction coefficient of P6 is 0.119.
[0095] The oil gels in Examples 4-9 and the PAO-10 base oil samples were subjected to the SRV-IV vibration reciprocating friction test. The wear volume under the same conditions was as follows: Fig.10 As shown, the details are as follows:
[0096] (1) Under the same conditions, compared with the PAO-10 base oil, the wear volume of the oil gel in Examples 4-9 was greatly reduced by up to 97%, and the wear scar on the wear surface was greatly reduced.
[0097] (2) With oil gel P6S 30 Compared with P6, oil gel Graphite@P6S 30 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance;
[0098] With oil gel P6S 50 Compared with P6, oil gel Graphite@P6S 50The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance;
[0099] With oil gel P6S 70 Compared with P6, oil gel Graphite@P6S 70 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance.
[0100] Therefore, the oil gels in Examples 4-9 can be used as lubricating oils, and the lubrication and anti-wear properties of the oil gels in Examples 7-9 are better than those in Examples 4-6.
[0101] Embodiment 10-12:
[0102] This embodiment is basically the same as Embodiments 7-9, except that graphene nanomaterials are used instead of graphite. Specifically, the details are as follows:
[0103] The graphene nanomaterial and the telechelic polymer P6S in Examples 1-3 are 30 P6, P6S 50 P6 and P6S 70 One of the P6 solid samples was dispersed in a poly-α-olefin-10 (PAO-10) base oil, with a telechelic polymer concentration of 6.0 wt% and a graphene nanomaterial concentration of 1.2 wt%. The base oil solution was heated and ultrasonicated, and π-π stacking interactions occurred between the pyrene groups at 20 °C to form an oil gel Graphene@P6S. 30 P6, Graphene@P6S 50 P6 and Graphene@P6S 70 P6.
[0104] The oil gels in Examples 4-6 and 10-12 and the PAO-10 base oil samples were subjected to SRV-IV vibration reciprocating tribology tests under the following test conditions: load 200N, frequency 25Hz, amplitude 1000μm, cycle 30min, temperature 20°C. The test results are shown in Fig.11 As shown, the details are as follows:
[0105] (1) Compared with the PAO-10 base oil, the friction coefficients of the oil gels in Examples 4-6 and 10-12 are all reduced, indicating that the addition of the telechelic polymer P6S to the PAO-10 base oil 30 P6, P6S 50 P6 and P6S 70 P6 can greatly improve its lubrication performance, that is, the oil gels in Examples 4-9 and Examples 10-12 can be used as lubricating oils.
[0106] (2) Compared with adding telechelic polymer to base oil, adding not only telechelic polymer but also graphene nanomaterial to base oil can further improve lubrication performance. For example, in Example 4, P6S 30 The friction coefficient of P6 is 0.123. 30 The friction coefficient of P6 is 0.118. 50 The friction coefficient of P6 is 0.123. 50 The friction coefficient of P6 is 0.118. 70 The friction coefficient of P6 is 0.124. 70 The friction coefficient of P6 is 0.118.
[0107] (3) Compared with the addition of telechelic polymer and graphene to the base oil in Examples 10-12, the lubricating properties of the oil gels formed by adding telechelic polymer and graphene to the base oil in Examples 7-9 are comparable. For example, Graphene@P6S 30 The friction coefficient of P6 is 0.118. 30 The friction coefficient of P6 is 0.119. Graphene@P6S in Example 11 50 The friction coefficient of P6 is 0.118. 50 The friction coefficient of P6 is 0.118. 70 The friction coefficient of P6 is 0.117. 30 The friction coefficient of P6 is 0.119.
[0108] The oil gels and PAO-10 base oil samples in Examples 4-6 and 10-12 were subjected to SRV-IV vibration reciprocating friction test. The wear volume under the same conditions was as follows: Fig.12 As shown, the details are as follows:
[0109] (1) Under the same conditions, compared with the PAO-10 base oil, the wear volume of the oil gels in Examples 4-6 and Examples 10-12 was greatly reduced by up to 97%, and the wear scars on the worn surfaces were greatly reduced.
[0110] (2) With oil gel P6S 30 Compared with P6, oil gel Graphene@P6S 30 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance.
[0111] With oil gel P6S 50 Compared with P6, oil gel Graphene@P6S 50 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance.
[0112] With oil gel P6S 70 Compared with P6, oil gel Graphene@P6S 70 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance.
[0113] Therefore, the oil gels in Examples 10-12 can be used as lubricating oils, and the lubrication performance and anti-wear performance of the oil gels in Examples 10-12 are better than those in Examples 4-6.
[0114] Embodiment 13-15:
[0115] Graphene oxide nanoparticles and the telechelic polymer P6S in Examples 1-3 30 P6, P6S 50 P6 and P6S 70 One of the P6 solid samples was dispersed in a poly-α-olefin-10 (PAO-10) base oil, with a telechelic polymer concentration of 6.0 wt% and a graphene oxide nanoparticle concentration of 1.2 wt%. The base oil solution was heated and ultrasonicated, and π-π stacking interactions occurred between the pyrene groups at 20 °C to form an oil gel GO@P6S. 30 P6, GO@P6S 50 P6 and GO@P6S 70 P6.
[0116] The oil gels in Examples 4-6 and 13-15 and the PAO-10 base oil samples were subjected to SRV-IV vibration reciprocating tribology tests under the following test conditions: load 200N, frequency 25Hz, amplitude 1000μm, cycle 30min, temperature 20°C. The test results are shown in Fig.13 As shown, the details are as follows:
[0117] (1) Compared with the PAO-10 base oil, the friction coefficients of the oil gels in Examples 4-6 and 13-15 are all reduced, indicating that the addition of the telechelic polymer P6S to the PAO-10 base oil 30 P6, P6S 50 P6 and P6S 70 P6 can greatly improve its lubrication performance, that is, the oil gels in Examples 4-9 and Examples 13-15 can be used as lubricating oils.
[0118] (2) Compared with adding telechelic polymer to base oil, adding not only telechelic polymer but also graphene oxide nanoparticles to base oil can further improve lubrication performance. For example, in Example 4, P6S 00 The friction coefficient of P6 is 0.123. 30 The friction coefficient of P6 is 0.12. 50 The friction coefficient of P6 is 0.123. 50 The friction coefficient of P6 is 0.121. 70 The friction coefficient of P6 is 0.124. In Example 15, GO@P6S 70 The friction coefficient of P6 is 0.12.
[0119] The oil gels in Examples 13-15 and the PAO-10 base oil samples were subjected to the SRV-IV vibration reciprocating friction test. The wear volume under the same conditions was as follows: Fig.14 As shown, the details are as follows:
[0120] (1) Under the same conditions, compared with the PAO-10 base oil, the wear volume of the oil gel in Examples 13-15 was greatly reduced by up to 97%, and the wear scar on the wear surface was greatly reduced.
[0121] (2) With oil gel P6S 30 Compared with P6, oil gel GO@P6S 30 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance;
[0122] With oil gel P6S 50 Compared with P6, oil gel GO@P6S 50 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance;
[0123] With oil gel P6S 70 Compared with P6, oil gel GO@P6S 70 The wear volume of P6 is reduced, showing smaller wear scars and improved anti-wear performance.
[0124] Therefore, the lubrication and anti-wear properties of the oil gels of Examples 13-15 are better than those of the oil gels of Examples 4-6.
[0125] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the lubrication performance and anti-wear performance of base oil, characterized by: The telechelic polymer is dispersed in the base oil to form supramolecular oil gel through π-π stacking interaction; The telechelic polymer is a polymethacrylate long-chain alkyl ester containing pyrene groups at both ends, denoted as P m S 2n P m , wherein the P block comprises 2-(1-pyrenebutanoyloxy)ethyl methacrylate monomer, the S block is an oil-soluble long-chain alkyl polymethacrylate, m is the degree of polymerization of the P block, and 2n is the degree of polymerization of the S block.
2. A method for improving the dispersion stability of graphite in base oil, characterized by: The telechelic polymer and graphite are dispersed in base oil to form supramolecular oil gel through π-π stacking interaction. Under the assistance of ultrasound, the π-π stacking interaction between the telechelic polymer pyrene group and graphite occurs, and the graphite is exfoliated into graphene in situ. The telechelic polymer is a polymethacrylate long-chain alkyl ester containing pyrene groups at both ends, denoted as P m S 2n P m , wherein the P block comprises 2-(1-pyrenebutanoyloxy)ethyl methacrylate monomer, the S block is an oil-soluble long-chain alkyl polymethacrylate, m is the degree of polymerization of the P block, and 2n is the degree of polymerization of the S block.
3. The method according to claim 1 or 2, characterized in that: m is an integer selected from 5 to 10, inclusive; Preferably, 2n is an integer selected from 10 to 500, including the integers 10 and 500; preferably, 2n is an integer selected from 10 to 100, including the integers 10 and 100, more preferably 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100; Preferably, the long-chain alkyl polymethacrylate includes lauryl polymethacrylate and octadecyl polymethacrylate; Preferably, the base oil includes mineral oil, synthetic oil and vegetable oil.
4. The method according to claim 1 or 2, characterized in that: The preparation method of the telechelic polymer comprises the following steps: (1) Synthesis of long-chain alkyl polymethacrylate based on bifunctional initiators; (2) Using long-chain alkyl polymethacrylate as a macromolecular ATRP initiator to synthesize dual-terminal hydroxyl-functionalized telechelic polymers; (3) Obtaining the pyrene functionalized telechelic polymer through esterification reaction.
5. The method according to claim 4, characterized in that: In the step (2), the hydroxyl group includes hydroxyethyl methacrylate and 2-methyl-2-acrylate-2,3-dihydroxypropyl ester.
6. The method according to claim 1 or 2, characterized in that: In the supramolecular oil gel, the mass percentage concentration of the telechelic polymer is 2-20%, preferably 5-10%, and more preferably 5%, 6%, 7%, 8%, 9% or 10%.
7. The method according to claim 2, characterized in that: In the supramolecular oil gel, the mass percentage concentration of graphite is 0.2-5%, more preferably 0.5-2.5%, and more preferably 0.5%, 1%, 1.5%, 2% or 2.5%.
8. The method according to claim 1 or 2, characterized in that: During the formation of the supramolecular oil gel, the base oil solution is heated at a temperature of 10-40° C., preferably 15-30° C., more preferably 15° C., 20° C., 25° C. or 30° C.; Preferably, during the formation of the supramolecular oil gel, the base oil solution is stirred, and more preferably ultrasonic stirring is used.
9. The method according to claim 2, characterized in that: The supramolecular oil gel has good lubrication and anti-wear properties; Preferably, when dispersed in the base oil PAO-10, the friction coefficient of the formed supramolecular oil gel under the friction conditions of a load of 200N and a frequency of 25Hz is less than 0.
12.
10. The method according to claim 1, characterized in that: When dispersed in the base oil PAO-10, the friction coefficient of the formed supramolecular oil gel is less than 0.125 under the friction conditions of a load of 200N and a frequency of 25Hz.
11. The method according to claim 1, characterized in that: It also disperses lubricant additives in the base oil; Preferably, the lubricating oil additive comprises graphite and its derivatives; Preferably, the graphite derivative includes one or more of graphene, graphene oxide, and reduced graphene oxide; Preferably, when dispersed in the base oil, the mass percentage concentration of the lubricating oil additive is 0.2-5%, more preferably 0.5-2.5%, and more preferably 0.5%, 1%, 1.5%, 2% or 2.5%.
12. The method according to claim 11, characterized in that: When the lubricating oil additive is graphite, ultrasound is used to assist in dispersion, and the graphite is in-situ exfoliated into graphene through the π-π stacking interaction between the telechelic polymer pyrene group and the graphite.
Citation Information
Cited By
Telechelic polymer, preparation method thereof, supramolecular oil gel and lubricating oil
CN119569972A
Telechelic polymers, methods for their preparation, supramolecular oleogels and lubricating oils
CN119569972B